2018
DOI: 10.1097/mat.0000000000000687
|View full text |Cite
|
Sign up to set email alerts
|

Leaflet Kinematics of Mechanical and Bioprosthetic Aortic Valve Prostheses

Abstract: The hemodynamic performance of artificial aortic valves (AVs) and the probability for structural valve deterioration can be linked to the valve kinematics. Comparability among different studies is limited because of variations in the experimental setups and physiologic boundary conditions. This study presents results of kinematic measurements of bioprosthetic and mechanical AVs that were tested in an identical experimental setting such that they can be directly compared with each other. The kinematics of AVs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 27 publications
8
26
0
Order By: Relevance
“…For the two mechanical valves advocating improved thromboresistance (i.e., the On‐X and Lapeyre‐Triflo), their design‐related features can contribute to thromboresistance . In contrast, the effect of material‐related features (i.e., surface properties) of the mechanical valves on their thromboresistance remains controversial.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For the two mechanical valves advocating improved thromboresistance (i.e., the On‐X and Lapeyre‐Triflo), their design‐related features can contribute to thromboresistance . In contrast, the effect of material‐related features (i.e., surface properties) of the mechanical valves on their thromboresistance remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it may be better to redesign the bileaflet shape of the PEEK‐ g ‐PMPC valve. In vitro studies revealed that traditional bileaflet designs show a behavior unlike bioprosthetic valves and generate non‐physiological flows in the cardiac cycle at the aortic position, which may trigger platelet activation . Taken together, the thromboresistance of a mechanical valve made of the thromboresistant material (i.e., PEEK‐ g ‐PMPC) requires improvement by a combination with design‐related thromboresistance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations